The Role of Higher Education in Egypt's Economic Development: Policy Analysis and Implementation - Husnul Haq (Innovative Journal of Educational Research and Insights, 2024)
This research investigates the role of higher education in fostering economic development in Egypt, focusing on policy implementation and the alignment of educational outcomes with market needs. The study utilizes a mixed-methods approach, combining quantitative surveys and qualitative semi-structured interviews with students, educators, and policymakers to explore perceptions of higher education's contribution to economic growth. The findings reveal that while Egypt's higher education system has made significant progress in increasing accessibility, there remain gaps in the relevance of education to the labor market. Regression analysis highlights a positive correlation between educational attainment and economic indicators, though skills mismatches persist. Case studies of successful university-industry partnerships underscore the importance of practical, hands-on learning and innovation in driving economic progress. Furthermore, comparisons with global best practices, particularly in South Korea and Finland, provide insights into potential policy reforms. Recommendations include enhancing university-industry collaboration, improving curriculum relevance, and investing in research and development to ensure higher education in Egypt supports sustainable economic growth